2020
DOI: 10.1016/j.jcp.2019.109061
|View full text |Cite
|
Sign up to set email alerts
|

A weight-adjusted discontinuous Galerkin method for the poroelastic wave equation: Penalty fluxes and micro-heterogeneities

Abstract: We introduce a high-order weight-adjusted discontinuous Galerkin (WADG) scheme for the numerical solution of three-dimensional (3D) wave propagation problems in anisotropic porous media. We use a coupled first-order symmetric stress-velocity formulation [1,2]. Careful attention is directed at (a) the derivation of an energy-stable penalty-based numerical flux, which offers high-order accuracy in presence of material discontinuities, and (b) proper treatment of micro-heterogeneities (sub-element variations) in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Compared to the direct implementation that is briefly described above, the proposed method reduces the memory requirement to 15KPML × Nq, where Nq ∼ Np, while maintaining the PML performance. It should be noted here that the WAA has been proved to be energy-stable and preserve the high-order convergence of DGTD [20]- [22]. Indeed, numerical examples presented here also show the proposed method maintains the higher-order accuracy of the solution.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Compared to the direct implementation that is briefly described above, the proposed method reduces the memory requirement to 15KPML × Nq, where Nq ∼ Np, while maintaining the PML performance. It should be noted here that the WAA has been proved to be energy-stable and preserve the high-order convergence of DGTD [20]- [22]. Indeed, numerical examples presented here also show the proposed method maintains the higher-order accuracy of the solution.…”
Section: Introductionsupporting
confidence: 51%
“…To reduce the memory requirement of implementing (15) with αuu(r) allowed to vary inside the elements, WAA [20] is used. It has been shown that with this approximation DGTD retains provable energy-stability and high-order accuracy [20]- [22]. Note that in the above SC-PML formulation, directly multiplying (5) and 6witḧ a −1 on both sides reduces the number of element-dependent mass matrices to 4.…”
Section: A Waa-dgtd For Sc-pmlmentioning
confidence: 97%
“…Besides, it is noteworthy that penalty fluxes, an alternative to upwind fluxes for dG methods, have also been developed in the literature [11,12,13,14]. To derive numerical fluxes, the penalty method is energy stable and significantly less complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Background information and references on numerical approaches to solving the poroelastic wave equation are given in [12] and is not repeated here. More recent work on numerical approaches to the poroelastic wave equation in the DF framework in three dimensions can be found in [25,30,31]. We also provided background on our motivation for studying poroelatic wave problems and the application to delineating aquifers from ground motion data.…”
Section: Introductionmentioning
confidence: 99%